Investigating students' attention span during synchronous online lectures - Tan, Tarif Tan Bin Zaki (Nanyang Technological University, 2023)
The optimum lecture duration, commonly derived from students’ attention spans, remains inconclusive in the extant literature. Research efforts have been focused on the context of face-to-face lectures and asynchronous online lectures, leaving a gap in knowledge regarding the ideal duration for synchronous online lectures. With the COVID-19 pandemic accelerating the adoption of synchronous online lectures, coupled with the difficulty of personalizing such lectures to students’ individual needs, addressing such a gap is crucial. Accordingly, the present study investigated the optimum duration by which synchronous online lectures should be continuously delivered to maximize students’ learning retention. Participants (N = 70) were randomly assigned to durations of continuous online lecture viewing (20 mins, 10 mins, & 6 mins 40 secs); viewing a 20-minute-long non-STEM lecture either in its entirety or in spaced segments. A multiple-choice questions test based on the lecture materials was administered, and test scores were analyzed via Bayesian statistical analyses. Findings revealed that lecture durations were not likely to affect students’ attention and learning, at least for non-STEM lectures. The effect of lecture duration was also independent of lecture segmentation – further deemphasizing the need for an ideal lecture duration to be identified. Individually, lecture segmentation was identified to have influenced participants’ scores – albeit in a manner that departed from established norms. Efforts to account for the findings obtained led to the identification of potential alternative factors influencing students’ attention during lectures (e.g., lecturers’ aptitude, salience of lecture information). It was further explored how these factors could be leveraged to improve students' learning during synchronous online lectures.